BOOK REVIEW - IPS, Editor (Indian Phytopathology, 2012)
Phytopathogenic Prockaryotes and Plant Diseases. B.S. Thind (ISBN: 978- 81-7233-780-3), Scientific Publishers, 5 A, New Pali Road, P.O. Box 91, Jodhpur - 342 001 (India), 2012, pp. 545, Price Rs. 375/-